Respon Masyarakat Terhadap Karya Sastra (Foklor) Studi Kasus Cerita Candi Tanjung Medan Kajian Dekonstruksi - Rico Aprisa (PT. Padang Tekno Corp, 2026)
Folklore is a reflection of social facts or real facts of the past which are the storyteller's response due to the inheritance and the common thread between the story and reality or rather there is an intertext in the patterns of inheritance of the story. This also occurs in the local community who call the Tanjung Medan temple as the Puti Sangkar Bulan temple. The story of Puti Sangkar Bulan is about two Rajo named Rajo Sangek Baung and Rajo Sabandar who are fighting over Puti Sangkar Bulan, so the temple is the place of their contest.